2023
DOI: 10.1177/08902070221145766
|View full text |Cite
|
Sign up to set email alerts
|

Filling gaps in the nomological networks for dominance and affiliation by examining self-informant agreement on momentary interpersonal behavior

Abstract: Interpersonal functioning involves an interplay of subjective perceptions and overt behavior. This study examines alignment between self and informant perceptions of momentary behavior to enrich the nomological networks for the domains of dominance and affiliation. We studied a sample of romantic couples ( N = 210 individuals) who rated their own and their partner’s interpersonal behavior during a 21-day ambulatory assessment (AA) protocol. We used multi-level structural equation modeling to estimate self-info… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Another limitation to consider is the shared method variance between AA variables and self-reports, which likely explains why more correlates emerged for girls’ reports. One alternative might be to use a yoked AA design, in which one person provides data about an event (e.g., conflict) and another is prompted to do the same (e.g., peers, caregivers; Ringwald et al, 2023). Because previous work has documented particularly high levels of informant discrepancies between caregiver- and adolescent-reports on questions about peer relationships (Kraemer et al, 2003), future studies further need to account for blind spots of both self- and caregiver-reports (e.g., by teacher-reports) to provide a more complete assessment of the diverse daily social contexts of youth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another limitation to consider is the shared method variance between AA variables and self-reports, which likely explains why more correlates emerged for girls’ reports. One alternative might be to use a yoked AA design, in which one person provides data about an event (e.g., conflict) and another is prompted to do the same (e.g., peers, caregivers; Ringwald et al, 2023). Because previous work has documented particularly high levels of informant discrepancies between caregiver- and adolescent-reports on questions about peer relationships (Kraemer et al, 2003), future studies further need to account for blind spots of both self- and caregiver-reports (e.g., by teacher-reports) to provide a more complete assessment of the diverse daily social contexts of youth.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, this line of research showed that particularly people with a BPD diagnosis relative to nonclinical and clinical controls report significantly greater variability in negative affect and interpersonal behaviors than nonclinical controls (Trull et al, 2008). More recent research suggests that even essential features of BPD are transdiagnostic, and that variability in socio-emotional processes may represent an indicator of general personality pathology (Ringwald et al, 2023). This builds on prior work investigating the daily manifestations of crosscutting dimensions of the DSM-5 personality disorder (PD) traits, suggesting that daily expressions of PDs in adults are highly variable, with half the total variability being associated with daily fluctuations (Wright & Simms, 2016).…”
Section: The Present Studymentioning
confidence: 99%
“…Assessing within-person temporal covariation patterns of internal states and plausibly evocative contextual factors directly targets the processes that clinicians have identified as key to symptom shifts among individuals with severe personality pathology (Pincus et al, 2009). Arguably, the most relevant context for the expression of personality pathology is the interpersonal context (Hopwood, 2018;Wright & Ringwald, 2022), and EMA methods are well suited to study the expression of PDs and, for instance, related cognitions (e.g., rumination; or expectancies (e.g., rejection sensitivity; Zeigler-Hill & Abraham, 2006) in such situations. Other constructs, such as urgency, are specifically defined as a contextualized process, and EMA can be used to directly study the within-person link between rash behavior and elevated emotions (Feil et al, 2020).…”
Section: Variabilitymentioning
confidence: 99%
“…Secondary data analyses:6 Carpenter et al, 2019;Fleming et al, 2021;Hepp et al, 2018;Napolitano et al, 2021 7 Kaurin et al, 2020bRingwald et al, 2022;Woods et al, 2020 8 Links et al, 2008Nisenbaum et al, 2010 …”
mentioning
confidence: 99%